2006
DOI: 10.1096/fj.05-5131fje
|View full text |Cite
|
Sign up to set email alerts
|

Vascular tenascin‐C regulates cardiac endothelial phenotype and neovascularization

Abstract: Microenvironmental cues mediate postnatal neovascularization via modulation of endothelial cell and bone marrow-derived endothelial progenitor cell (EPC) activity. Numerous signals regulate the activity of both of these cell types in response to vascular injury, which suggests that parallel mechanisms regulate angiogenesis in the vascular beds of both the heart and bone marrow. To identify mediators of such shared pathways, in vivo bone marrow/cardiac phage display biopanning was performed and led to the ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 49 publications
2
50
0
1
Order By: Relevance
“…The presence of Tn-X+ and Tn-C+ was confirmed in some blood vessels in the parenchyma of the cerebellum and medulla oblongata ( Figure 2C, E). These results were consistent with previous reports of vascular localization of Tn-X and Tn-C (Matsumoto et al, 1994;Hasegawa et al, 1997;Ballard et al, 2006). In addition, a leptomeningeal Tn-X+ trabecular structure was also observed in the cerebellum ( Figure 2C).…”
Section: Resultssupporting
confidence: 93%
“…The presence of Tn-X+ and Tn-C+ was confirmed in some blood vessels in the parenchyma of the cerebellum and medulla oblongata ( Figure 2C, E). These results were consistent with previous reports of vascular localization of Tn-X and Tn-C (Matsumoto et al, 1994;Hasegawa et al, 1997;Ballard et al, 2006). In addition, a leptomeningeal Tn-X+ trabecular structure was also observed in the cerebellum ( Figure 2C).…”
Section: Resultssupporting
confidence: 93%
“…24 Our in vitro experiment revealed that lacking osteopontin inhibited phosphorylation of Smad3 and p38 in cultured ocular fibroblasts that might explain the mechanism of attenuation of TGFb-related fibrogenic reaction in osteopontin-null fibroblasts. 25 As for the mechanism of impairment of TGFb-related healing and fibrogenic gene expression by the loss of tenascin C was reported in experimental lung fibrosis model in mice, [26][27][28][29] this report also showed that lacking tenascin C decreases the level of total Smad3 (not Smad2), 30 but did not inhibit the phosphorylation of Smad3, as examined by western blotting. The authors of this report speculate that reduction of total Smad3 protein might account for the impairment of TGFb/ Smad3 signal and resultant inhibition of fibrogenic behaviors of fibroblasts in lung tissue.…”
Section: Discussionmentioning
confidence: 97%
“…28 In addition, endothelial cells and vascular smooth muscle cells of various organs have the potential to synthesize TN-C under these same stimulations. 10,29 The elevated levels of circulating soluble inflammatory mediators in heart failure patients might also stimulate endothelial cells of, for example, the liver, or lung, to secrete TN-C into the blood stream.…”
Section: Discussionmentioning
confidence: 99%